Most Probable Number (MPN) Coliform of Jamu Gendong Kencur Rice in Traditional Markets in Sukoharjo Region - Jamilatun, Makhabbah (UIN Syarif Hidayatullah Jakarta, 2025)
One of the traditional medicines that is very popular with the public because it is affordable and easy to obtain in both traditional and modern markets is herbal medicine. Among the various types of herbal medicine circulating in the community, the one most frequently encountered is jamu carrying kencur rice. The safety of traditional medicinal products (herbal medicine) is a demand that has been put forward since the emergence of human health problems due to contamination by microorganisms, such as coliforms. Microbiological examination of water is very necessary to prevent contamination of water consumed by humans. This research aims to determine the contamination of coliform bacteria in the kencur rice herbal medicine in traditional markets in the Sukoharjo area. The method used in this research is the MPN (Most Probable Number) method which consists of two stages, namely the presumptive test and the confirmed test. The results showed that samples with codes 1, 2, 5, 6, 7, 8, 11, and 12 had an MPN value of 0/100 ml. Furthermore, samples with codes 3, 4, 9, and 10 show MPN values > 0/100 ml. Based on the research results, samples that meet good drinking water quality based on the Regulation of the Minister of Health of the Republic of Indonesia, are samples with codes 1, 2, 5, 6, 7, 8, 11, and 12, while samples with codes 3, 4, 9, 10 do not meet the requirements.